INFLUENCE OF MATURATION ON ENGINEERING PROPERTIES OF THREE BEAN (PHASEOLUS VULGARIS L.) VARIETIES, RELATED TO MACHINE DESIGN - Prosper, Oghenerukevwe; Uguru, Hilary (International Journal of Research -GRANTHAALAYAH, 2018)
Knowledge of the engineering properties of seeds is essential for the design and development of their harvesting, handling and processing machines. Engineering properties of post-harvest bean seeds have been well studied, but the influence of maturation on the engineering properties of most crops including bean seeds have not been fully studied. The objective of this study was to determine the effect of maturity stage on some engineering properties of three bean varieties (butter, brown and white cowpea) grown in Nigeria. The bean seeds were harvested at 15, 20 and 25 days after flowering, and these engineering properties; average thousand seed mass, size, volume, geometric mean, sphericity, surface area, arithmetic mean, bulk density, true density, porosity, coefficient of static friction, hydration capacity and coefficient, and swelling capacity and coefficient were investigated. The results showed that maturity stage of the bean seeds significantly (P≤ 0.05) affects all their studied. Correlations between the engineering properties and maturity stage for the three bean varieties were relatively high. Over the course of a maturation time, the moisture content declined from 83.40 to 42.31, 86.59 to 46.73, and 87.15 to 47.82 % (wb) for butter, white cowpea and brown bean seeds respectively. From the results, the ideal period for bean pods harvest, processing and handling for the three bean varieties is between 20 to 25 days after anthesis, since the seeds will be having maximum dry weight and higher viability. The results gotten from this research are important in the design and development of processing and handling machines.